Lignocellulolitic enzymes production: an important phenomenon for the production of citric acid from lignocellulosic substrate through solid state bioconversion - Bari, Md. Niamul; Alam, Md. Zahangir; Muyibi, Suleyman Aremu; Jamal, Parveen; Al-Mamun, Abdullah (2009)
An investigation was carried out to determine the production of lignocellulitic enzymes: ligninase and cellulases (exo-cellulase and edo-cellulase) and their effects during the bioconvertion of empty fruit bunches (EFB) for the production of citric acid. The result shows that the maximum production of citric acid was 181.25 g/kg of dry EFB from A. niger IBO-114MNB after 8 days of bioconversion, 152.4 g/kg of dry EFB from A. niger IBO-103MNB after 6 days of bioconversion and 103.8 g/kg of dry EFB from A. niger IBO-109MNB after 6 days of bioconversion with the exo-cellulase production of 4.9 FPU/g EFB, 4.5 EFU/g EFB and 2.3 FPU/ g EFB as well as endo-cellulase was produced 8.6 CMC/g EFB, 8.3 CMC/g EFB and 3.8 CMC/g EFB, respectively. At the same time ligninase production was 6707.9 U/g EFB, 5020 U/g EFB and 3333 U/g EFB from IBO-103MNB, IBO-114MNB and IBO-109MNB, respectively. The degradation of cellulose and hemicelluloses content were 15.5-23.3% of initial contents that contribute 115-173 g sugar from 1 kg of dry EFB.